Copolymerization approach of soft segment towards the adhesion improvement of polycarbonate-based thermoplastic polyurethane. Issue 15 (18th November 2021) - Wongsamut, Chompunut; Demleitner, Martin; Suwanpreedee, Rachaneewan; Altstädt, Volker; Manuspiya, Hathaikarn
ABSTRACT: Thermoplastic polyurethane elastomers (TPUs) have been intensively used as hot-melt adhesives (HMAs) due to their adherence ability that can be applied on hard surfaces. To overcome their drawbacks, such as low peel strength and deformation, the performance improvement of the TPUs-HMAs has become a challenging issue. In this study, the enhancement properties of the TPUs-HMAs were achieved from the copolymerization of a soft-segment technique. Two types of polycarbonate diols (PCDs) were utilized for the TPU production as a co-diol of the soft segment. The properties and phase behaviour of the TPUs with various ratios of copolymerized soft segment were analysed. The compatibility between the different types of the PCDs is defined by the concentration of the hydrogen bonding interaction between the hard and soft phases and the dimensions of the hard domains. The homogeneous dispersion of the hard domains in the soft phase promotes better stress transfer enhancing the mechanical properties and adhesion properties. The peel strength is measured between the TPUs/stainless steel joint, in which the highest value is accomplished with the formulation of 60:40 wt% of copolymerized soft segment, which is associated with the superior mechanical strength and the optimum compatible properties of the soft segment.